(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis explores the effectiveness of digital educational technologies in enhancing the quality of teaching and learning processes. It examines how the integration of digital tools—such as learning management systems, interactive platforms, virtual classrooms, and artificial intelligence—can improve student engagement, facilitate personalized learning, and support teachers in delivering content more efficiently. The study also identifies key challenges in the implementation process and provides practical recommendations for successful integration of digital technologies in both traditional and online educational environments.